PENGGUNAAN TEKNIK MOZAIK DALAM PEMBELAJARAN SENI RUPA UNTUK MENINGKATKAN KREATIVITAS ANAK KELAS IV UPTD SD NEGERI BALFAI KABUPATEN KUPANG - Zacharias, Sueliyam; Djokaho, Margaret; Koro, Maxsel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the use of Mosaic Technique in learning fine arts to improve the creativity of fourth grade students of UPTD SD Negeri Balfai, Kupang Regency. The type of research used is classroom action research with stages, namely planning, implementation, observation, testing and reflection. This research was conducted at UPTD SD Negeri Balfai with subjects of 23 fourth grade students, namely 12 boys and 11 girls. Data collection was carried out using observation, testing and documentation techniques. The collected data were further analyzed using comparative descriptive data analysis techniques. Student learning outcomes increased from Pre-Cycle, Cycle I to Cycle II. In the Pre-Cycle, the presentation of student learning outcomes reached 21.73% with 5 students achieving the Learning Objective Completion Criteria (KKTP). In Cycle I, the presentation of student learning outcomes reached 56.52% with 13 students achieving the Learning Objective Completion Criteria (KKTP). While in Cycle II it reached 100% with 23 students achieving the Learning Objective Completion Criteria (KKTP). In addition, there was an increase in the average recapitulation value of student learning outcomes from 61.08 in the Pre-Cycle, increasing to 65.83 in Cycle I, to 93.47 in Cycle II. Based on the research results above, it can be concluded that by using Mosaic Technique in Fine Arts learning, it can increase children's creativity.